(untitled) (Research, Society and Development, 2021)
Feline lower urinary tract disease (FLUTD) is a common problem in clinical routine, resulting in a change in urination pattern. Urethral obstruction in cats fits into FLUDT and represents high risk to life, occuring mainly by the formation of uroliths that stop urinary flow, being able to trigger post renal azotemia and obstructive acute kidney failure. There are many hypothesis about the formation and development of urolithiasis, but none of them are very clear, as it can happen alone or simultaneously. Over the years, the urolith type prevalence in felines has been modified, mainly because of dietary changes implemented to prevent the emergence of struvite uroliths, which increased the cases of calcium oxalate in cats. The current paper has the purpose of contributing to the understanding of the pathophysiology involved in the formation of the main two kinds of urolithiasis in the feline species and assist in the diagnosis, treatment and prevention of each case.